Assessment of a landfill methane emission screening method using an unmanned aerial vehicle mounted thermal infrared camera – A field study. (15th March 2019) - Fjelsted, L.; Christensen, A.G.; Larsen, J.E.; Kjeldsen, P.; Scheutz, C.
Highlights: Thermal infrared (TIR) camera as screening tool for landfill gas emission hotspots. Temperature differences in the TIR images was limited to between 0.7 °C and 1.2 °C. There is a lower limit for landfill gas emission to be detected by TIR camera. Landfill gas emissions influenced by barometric pressure gradient. Abstract: An unmanned aerial vehicle (UAV)-mounted thermal infrared (TIR) camera's ability to delineate landfill gas (LFG) emission hotspots was evaluated in a field test at two Danish landfills (Hedeland landfill and Audebo landfill). At both sites, a test area of 100 m 2 was established and divided into about 100 measuring points. The relationship between LFG emissions and soil surface temperatures were investigated through four to five measuring campaigns, in order to cover different atmospheric conditions along with increasing, decreasing and stable barometric pressure. For each measuring campaign, a TIR image of the test area was obtained followed by the measurement of methane (CH4 ) and carbon dioxide (CO2 ) emissions at each measuring point, using a static flux chamber. At the same time, soil temperatures measured on the surface, at 5 cm and 10 cm depths, were registered. At the Hedeland landfill, no relationship was found between LFG emissions and surface temperatures. In addition, CH4 emissions were very limited, on average 0.92–4.52 g CH4  m −2  d −1, and only measureable on the two days with decreasing barometric pressure. TIR images from Hedeland did not show any significant temperature differences in the test area. At the Audebo landfill, an area with slightly higher surface temperatures was found in the TIR images, and the same pattern with slightly higher temperatures was found at a depth of 10 cm. The main LFG emissions were found in the area with the higher surface temperatures. LFG emissions at Audebo were influenced significantly by changes in barometric pressure, and the average CH4 emissions varied between 111 g m −2  d −1 and 314 g m −2  d −1, depending on whether the barometric pressure gradient had increased or decreased, respectively. The temperature differences observed in the TIR images from both landfills were limited to between 0.7 °C and 1.2 °C. The minimum observable CH4 emission for the TIR camera to identify an emission hotspot was 150 g CH4  m −2  d −1 from an area of more than 1 m 2 .